Wedge-shaped vertebrae is a risk factor for symptomatic upper lumbar disc herniation - Feng Wang; Zhen Dong; Yi-peng Li; De-chao Miao; Lin-feng Wang; Yong Shen (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background At present, much is unknown about the etiology and pathogenesis of ULDH. However, it is interesting to note that many ULDH patients have a radiographic feature of adjacent vertebral wedge deformation. The purpose of this study is to investigate the relationship between symptomatic upper lumbar disc herniation (ULDH) and wedge-shaped vertebrae (WSV). Methods This was a retrospective study of 65 patients with single-level ULDH, who had undergone surgery at our medical center between January 2012 and December 2016. Clinical data including clinical and radiological evaluation results were performed. Results The incidence of WSV in the ULDH group (44.6%, 29/65) was more than in the lower lumbar disc herniation group (21.5%, 14/65). And there were statistically significant differences in WSV (χ 2 = 7.819, P = 0.005), wedging angle of the vertebrae (WAV) (t = 9.013, P < 0.001), and thoracolumbar kyphotic angle (TL) (t = 8.618, P < 0.001) between two groups. Based on multivariate logistic regression analysis, WAV (OR = 0.783, 95% CI = 0.687–0.893, P < 0.001) and TL (OR = 0.831, 95% CI = 0.746–0.925, P = 0.001) were independently associated with ULDH. The cutoff values of WAV and TL were 5.35° and 8.35°, which were significantly associated with ULDH (OR = 3.667, 95% CI = 1.588–8.466, P = 0.002). Conclusion The WSV is an independent risk factor for ULDH. WAV > 5.35° and TL > 8.35° were the predictors for ULDH. It should be noted that the patients with vertebral wedge deformation combined with thoracolumbar kyphosis have a higher risk of ULDH.